Right Cortical Activation During Generation of Creative Insights: An Electroencephalographic Study of Coaching - Bartolomé, Gorka; Vila, Sergi; Torrelles-Nadal, Cristina; Blanco, Eduardo (Frontiers in Education, 2022)
Coaching as a human development methodology has been demonstrating its results for more than four decades. Even so, the level of confusion about its essence and its lack of a definitive theoretical and methodological framework has caused its effectiveness to be questioned. Although studies on coaching with neuroimaging methodologies have been developed, there is no recent evidence about the brain changes in electroencephalographic (EEG) activity during a coaching session. The present research aims to make a comparison between EEG measurements of three different conditions, namely, rumination (R), directive (DC), and non-directive coaching (NDC), during the process of problem solving and goal achievement. Our hypothesis was that the use of the meta-competencies of NDC should induce a higher activation of brain mechanisms that facilitate the insight process, therefore causing an improvement in creative capacity. Results showed significant changes in alpha and theta frequencies in the right temporal region, and alpha, theta, and gamma in the right parietal region in the NDC condition compared to other experimental conditions. The correct use of the meta-competencies of NDC facilitates the rise of insight and the generation of creativity processes at the brain level. Thus, the application of the methodological framework of the NDC was related, in a specific way, to the creativity and the development of human knowledge.